Feeding Patterns and Xenomonitoring of Trypanosomes among Tsetse Flies around the Gashaka-Gumti National Park in Nigeria - Solomon Ngutor Karshima; Idris A. Lawal; Oluseyi Oluyinka Okubanjo (Journal of Parasitology Research)
In order to understand the epidemiology of trypanosomoses in Gashaka-Gumti National Park, Nigeria, we determined the density, infection rates, and feeding patterns of tsetse flies using biconical traps, ITS, and mitochondrial cytochrome b PCRs. A total of 631 tsetse flies were captured, of which 531 (84.2%) and 100 (15.8%) were analyzed for trypanosomes and blood meals, respectively. Tsetse distribution varied significantly (p<0.05) across study sites with average trap and daily catches of 4.39 and 26.34, respectively. Overall tsetse infection rate was 5.08% and ranged between 3.03% and 6.84% across study sites. We identified 10 T. brucei, 3 T. congolense savannah, 2 T. congolense forest, and 2 mixed infections among the 13 pools made from the 27 flies positive for trypanosomes with light microscopy. The distribution of vertebrate blood meals in tsetse flies varied significantly (p<0.05) and ranged between 6.0% and 45% across hosts. We also observed dual feeding patterns involving at least 2 hosts in 24% and multiple feeding involving at least 3 hosts in 17% of the flies. We observed predominance of G. palpalis which also recorded higher infection rate. T. brucei was more prevalent among tsetse flies. Tsetse flies fed predominantly on cattle and less frequently on humans and also showed mixed feeding habits.